IMPLEMENTASI PRINSIP GOOD CORPORATE GOVERNANCE DALAM PELAYANAN KPR FLPP PADA BRI BRANCH OFFICE TANJUNG KARANG - Robiyansyah; M. Yusuf Sulfarano Barusman (Jurnal Riset Multidisiplin Edukasi, 2026)
The implementation of good governance principles in public service delivery is a fundamental requirement for achieving effective, accountable, and citizen-oriented services. In the banking sector, these principles are particularly crucial when banks act as implementing agents for government programs, especially subsidized home ownership credit through the Housing Financing Liquidity Facility (FLPP). This study aims to analyze the implementation of good governance principles in FLPP mortgage services at PT Bank Rakyat Indonesia Branch Office Tanjung Karang. This research employs a qualitative descriptive approach. Data were collected through in-depth interviews, observation, and document analysis involving internal bank officers and FLPP beneficiaries. Findings indicate that transparency, accountability, and responsibility have been implemented adequately through clear information disclosure, standardized service procedures, and intensive customer assistance. However, several challenges remain, including limited customer understanding of financing mechanisms and inconsistencies in service delivery across different stages. These findings suggest that effective implementation of good governance depends not only on regulatory frameworks and SOPs but also on human resource capacity and service communication. This study contributes empirically to the discourse on good governance practices in the banking sector, particularly in subsidized housing programs.